2018
DOI: 10.1016/j.gerinurse.2017.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Fear of falling among community-dwelling older adults: A scoping review to identify effective evidence-based interventions

Abstract: Fear of falling presents a significant problem for many older adults by reducing physical function and increasing the risk of future falls. Several different types of interventions have improved fear of falling and a summary of efficacious interventions will help clinicians recommend treatment options. Using the Arksey and O'Malley Framework for scoping reviews, the purpose of this review was to identify efficacious interventions for treating fear of falling among community-dwelling older adults in order to pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
53
0
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(59 citation statements)
references
References 62 publications
(116 reference statements)
0
53
0
6
Order By: Relevance
“…Nevertheless, for many participants – especially those living in houses and apartments without transportation and private home care insurance – regular exercise classes, physiotherapy, and fall prevention programs were neither affordable nor accessible. Given the proven benefits of interventions for falls and fear of falling (e.g., Whipple, Hamel, & Talley, 2018 ), it is essential to develop strategies to make those programs more available. Policies in aging, health, and social services should support greater collaboration between community-based formal and informal care ( Ryser & Halseth, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, for many participants – especially those living in houses and apartments without transportation and private home care insurance – regular exercise classes, physiotherapy, and fall prevention programs were neither affordable nor accessible. Given the proven benefits of interventions for falls and fear of falling (e.g., Whipple, Hamel, & Talley, 2018 ), it is essential to develop strategies to make those programs more available. Policies in aging, health, and social services should support greater collaboration between community-based formal and informal care ( Ryser & Halseth, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…The importance of maintaining good physical performance in old age has been demonstrated by several studies [25][26][27][28] . Den Ouden et al 25 , in a 10-year prospective study, observed that muscle strength, associated with number of chronic diseases, age, sex (female) and socioeconomic status, was a determining factor for dependence on daily living activities in community-dwelling older adults.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of physical training alone in psychological variables, such as fear of falls, for example, are controversial. According to Whipple et al 28 , multiple interventions are most effective in reducing the fear of falls, especially when involving multimodal physical training and cognitive behavioral intervention. Freiberger et al 29 conducted a randomized clinical trial to evaluate the effect of three different interventions on older adults with a history of falls and fear of falls.…”
Section: Discussionmentioning
confidence: 99%
“…Auch auf die Sturzangst haben reine Trainingsinterventionen nur einen geringen bis moderaten kurzfristigen positiven Effekt [45]. Wirksamere Interventionen zur Reduktion von Sturzangst kombinieren in der Regel Trainingskomponenten (Kraft und Balance oder Tai Chi) mit kognitiv behavioralen Interventionen [46]. Hauptkomponenten des bekanntesten Interventionsansatzes zur Reduktion von Sturzangst ("Matter of Balance") [47] sind zum Beispiel das Erkennen und Überwinden dysfunktionaler sturzbezogener Kognitionen, die Verbesserung der sturzbezogenen Kontrollwahrnehmung, das Setzen realistischer (sich steigernder) Aktivitätsziele zur Stärkung der sturzbezogenen Selbstwirksamkeit, die Modifikation von Sturz-Risikofaktoren sowie die Verbesserung von Kraft und Balance durch körperliches Training.…”
Section: Relevanz Und Klinische Implikationenunclassified
“…Dennoch spielen Interventionen mit kognitiv behavioralen Komponenten in der Versorgung in Deutschland bislang keine Rolle. Trotz der Relevanz von Sturzangst und einer Reihe vielversprechender Ansätze gibt es bislang noch keine klaren Empfehlungen zu Screening und Intervention in der Versorgungsroutine [46].…”
Section: Relevanz Und Klinische Implikationenunclassified